2019
DOI: 10.3390/membranes9050059
|View full text |Cite
|
Sign up to set email alerts
|

Concentrating of Sugar Syrup in Bioethanol Production Using Sweeping Gas Membrane Distillation

Abstract: Membrane distillation (MD) is a relatively new and underdeveloped separation process which can be classified as a green technology. However, in order to investigate its dark points, sensitivity analysis and optimization studies are critical. In this work, a number of MD experiments were performed for concentrating glucose syrup using a sweeping gas membrane distillation (SGMD) process as a critical step in bioethanol production. The experimental design method was the Taguchi orthogonal array (an L9 orthogonal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Forced convection of gas increases the rate of evaporation [4], which was confirmed by the results presented in Figure 8 (Tests 1 and 2-without feed pre-heating), showing that the permeate flux increased from 0.240 to 0.385 L/m 2 h (60%) when the fan was started and air was flowing between the capillaries at a velocity of 1.8-2.5 m/s. A similarly large effect of increasing the gas flow velocity was demonstrated in SGMD modules with a shell [20,32]. However, the process efficiencies obtained for such classical modules are presented in a wide range of 0.1-50 L/m 2 h [4, 16,22].…”
Section: Effect Of Gas Flow Ratementioning
confidence: 95%
See 2 more Smart Citations
“…Forced convection of gas increases the rate of evaporation [4], which was confirmed by the results presented in Figure 8 (Tests 1 and 2-without feed pre-heating), showing that the permeate flux increased from 0.240 to 0.385 L/m 2 h (60%) when the fan was started and air was flowing between the capillaries at a velocity of 1.8-2.5 m/s. A similarly large effect of increasing the gas flow velocity was demonstrated in SGMD modules with a shell [20,32]. However, the process efficiencies obtained for such classical modules are presented in a wide range of 0.1-50 L/m 2 h [4, 16,22].…”
Section: Effect Of Gas Flow Ratementioning
confidence: 95%
“…Conducting the SGMD process in small modules and at relatively high flows does not cause significant changes in the feed temperature [26]. Hence, in some studies a slight influence of the feed flow velocity was shown [26,32], which, however, changes when modules with a much larger membrane area are tested [10,17,20].…”
Section: Influence Of Process Parameters On the Permeate Fluxmentioning
confidence: 99%
See 1 more Smart Citation
“…To develop high quality membrane for the membrane distillation process, the knowledge of membrane characteristics is very important. [8][9][10][11] Although, the basic characteristics of high quality membranes are hydrophobicity and microporosity. The hydrophobicity is required to restrict the passage of liquid; hydrophobicity must be as high as possible to make a well-controlled membrane.…”
Section: Membrane Characteristicsmentioning
confidence: 99%
“…Bioethanol is generated, starting from renewable materials through saccharification and fermentation processes, and its production is linked to the sugar content in the prehydrolyzates. Sweep Gas Membrane Distillation (SGMD) was used to concentrate glucose syrup and the parameters that mostly affected the permeate flux were identified [ 7 ]. Feed temperature and sweep gas flow rate had the most significant impact; however, in all tests, 99% of glucose rejection was registered, confirming the efficiency of the process for obtaining concentrated glucose streams.…”
mentioning
confidence: 99%